Status Perceptions Matter: Understanding Disliking Among Adolescents. (27th October 2015) - Pál, Judit; Stadtfeld, Christoph; Grow, André; Takács, Károly
Abstract : The emergence of disliking relations depends on how adolescents perceive the relative informal status of their peers. This phenomenon is examined on a longitudinal sample using dynamic network analysis (585 students across 16 classes in five schools). As hypothesized, individuals dislike those who they look down on (disdain), and conform to others by disliking those who they perceive as being looked down on by their peers (conformity). The inconsistency between status perceptions also leads to disliking, when individuals do not look up to those who they perceive to be admired by peers (frustration). Adolescents are not more likely to dislike those who they look up to (admiration). The results demonstrate the role of status perceptions on disliking tie formation.